Transportation networks and the location of human activities - Dominique Peeters; Jacques Thisse; Isabelle Thomas (European Regional Science Association (ERSA), 1998)
The impact of transportation networks on the location of human activities is a surprisingly neglected topic in economic geography. Using the simple plant location problem, this paper investigates such an impact in the case of a few idealized networks. It is seen that a grid network tends to foster a dispersed pattern of activities, while the center of a radial network acts as an attractor. The case of two economies characterized by different network configurations that form a custom union is then analyzed. It is shown that the structural properties of the networks still hold, though some locations are pulled toward the common border. This suggests that no much relocation should be expected within the European Union if the state members endorse similar fiscal and social policies after the formation of the single market.
Keywords: 330